In memory of Professor Wolfgang Förster and Professor Zdzislaw Hellwig - Fleischer, Karlheinz (Pamięci Profesora Wolfgang Förstera i Profesora Zdzisława Hellwiga, 2020)
In September 2019, the 25th Joint Statistical Seminar of the Philipps University of Marburg and the Wroclaw University of Economics was held. Therefore some (more or less) interesting facts about these 25 meetings are summarized here as far as they could be reconstructed from the files of one of the founders of these seminars
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2020, Nr 18 (24), s. 33-37